2021
DOI: 10.3390/atmos12050611
|View full text |Cite
|
Sign up to set email alerts
|

Mass Concentration, Chemical Composition, and Source Characteristics of PM2.5 in a Plateau Slope City in Southwest China

Abstract: In order to investigate the seasonal variations in the chemical characteristics of PM2.5 at the plateau slope of a mountain city in southwest China, 178 PM2.5 filters (89 quartz and 89 Teflon samples for PM2.5) were collected to sample the urban air of Wenshan in spring and autumn 2016 at three sites. The mass concentrations, water-soluble inorganic ions, organic and inorganic carbon concentrations, and inorganic elements constituting PM2.5 were determined, principal component analysis was used to identify pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…In comparison to other Chinese studies, most of the ionic species identified in the research are found to be on the lower side. Compared with Kunming [30] and Wenshan [40], the concentration of SO 4 2− was lowest, which is consistent with the lagged industrial development of Baoshan. These results show that the WSII concentrations in Baoshan were impacted more by local pollution sources (e.g., biomass burning, agricultural dust, construction dust, etc.)…”
Section: Characteristics Of Pm 25supporting
confidence: 69%
See 2 more Smart Citations
“…In comparison to other Chinese studies, most of the ionic species identified in the research are found to be on the lower side. Compared with Kunming [30] and Wenshan [40], the concentration of SO 4 2− was lowest, which is consistent with the lagged industrial development of Baoshan. These results show that the WSII concentrations in Baoshan were impacted more by local pollution sources (e.g., biomass burning, agricultural dust, construction dust, etc.)…”
Section: Characteristics Of Pm 25supporting
confidence: 69%
“…These values are lower than those of developed cities in the plains of China, such as Beijing and Tianjing [38]. Furthermore, the concentration of PM 2.5 in Baoshan was lower than that in some plateau cities, such as Guiyang, Wenshan, and Kunming [30,39,40]. At the same time, it can be seen in Figure 2 that although the air quality in Baoshan was better than that in domestic cities, there is still a certain gap in comparison to foreign cities, such as New York [41].…”
Section: Characteristics Of Pm 25mentioning
confidence: 99%
See 1 more Smart Citation
“…The average concentration of the four water-soluble ions and two gases during the sampling period was 6.855 µg/m 3 , with SO 4 2− , NO 3 − , and NH 4 + (collectively referred to as SNA) being the most abundant. These results are consistent with those of Shi et al [22]. During the sampling period, the ratio of the mass concentration of SNA to the total water-soluble ion content in Wuhan (excluding HCl, HNO 2 , HNO 3 , SO 2 , and NH 3 ) was 88.37%.…”
Section: Concentration Of Water-soluble Ions Over Timesupporting
confidence: 92%
“…more significant between Harbin and Qiqihar. Consequently, it is apparent that PM2.5 has weak transmission capacity [43][44][45], with a relatively limited spatial distribution range, especially under static and stable weather conditions, predominantly affected by local regional pollution sources.…”
Section: Spatial Variation Characteristics Of O 3 and Pm 25mentioning
confidence: 99%